Proximal femoral nail- outcome and complications: a prospective study of 125 cases of proximal femoral fractures - Chopra, B. L.; Kumar, Krishan; Khajotia, B. L.; Bhambu, Ravindra; Bhatiwal, Sunil; Shekhawat, Vikrant (International Journal of Research in Orthopaedics, 2017)
Background: Fractures of the proximal femur are relatively common injuries in adults and common source of morbidity and mortality among the elderly. Fractures of the proximal femur include trochantric and subtrochantric fractures. The present study was designed to evaluate and analyze the role of proximal femoral nail (PFN) in the treatment of proximal femoral fractures. Methods: It was a prospective study on 125 cases of proximal femoral fractures. The fractures were classified according to AO classification. Salvati and Wilson Score were used for functional assessment. Results: In this study at 6 months follow up, union was achieved in 123 cases, open reduction was performed in 11% of cases (14 cases). Technical and mechanical complications were noted in 21% cases (27 cases). Reoperation rate was 4% (Five cases). According to Salvati and Wilson scoring system excellent results were seen in 36% of cases (45 cases), good results in 46% cases (58 cases), fair result in 13% cases (16 cases) and poor results in 5% cases (6 cases). Conclusions: It is concluded from our study that proximal femoral nailing is an attractive and suitable implant for Proximal Femoral Fractures and its use in unstable intertrochantric fractures is very encouraging.